Effectiveness of Pugun Tanoh Leaves Ethanol Extract (Curanga fel-terrae (Lour.) Merr) as an Anti-inflammation in Patients after Tooth Extraction at Dental and Mouth Hospital of Dentistry Faculty, Universitas Sumatera Utara - Rusdy, Hendry; Marianne, Marianne; Gurning, Baginda Mangatur (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Pugun Tanoh (Curanga fel-terrae (Lour.) Merr) is one of the medicinal plants. C. fel-terrae often used by the Karo tribe of Tiga Lingga Village, Kabupaten Dairi, Provinsi Sumatera Utara to treat diarrhea, asthma, cough, scabies, inflammation, bruising, and abdominal pain. Hence, it is necessary to examine the anti-inflammatory effects of Pugun Tanoh leaf extract. AIM: The present study aimed to determine the effectiveness of Pugun Tanoh leaves ethanol extract as an anti-inflammatory in patients after tooth extraction at Dental and Mouth Hospital of Dentistry Faculty, Universitas Sumatera Utara. METHODS: There were two research groups, namely the treatment group, which was given the extract plus amoxicillin 500 mg and mefenamic acid 500 mg as well as the control group who were only given amoxicillin 500 mg and mefenamic acid 500 mg without the extract. However, the instructions given to the patient are only required to take 500 mg of amoxicillin as an antibiotic, but for the 500 mg mefenamic acid drug, it is only instructed to drink it if there is pain that is felt by the patient. After the extracted teeth, the treatment group was given C. fel-terrae leaves ethanol extract 1.1 mg/kg on the tooth extraction socket using a 3 ml syringe then measurements were made on day 1 and day 2 after the extract was given using a visual analog scale (VAS) and through direct observation. Statistical analysis using the t-test independent and Chi-square test (significant p < 0.05). RESULTS: The treatment group did not have signs of inflammation both on the 1st and 2nd days after tooth extraction, while the control group had signs of inflammation both on the 1st day and the 2nd day after tooth extraction. In the treatment group, there were no patients who took the mefenamic acid drug while in the control group, it was found that all patients took mefenamic acid because they felt post-extraction pain. Statistical result are obtained with p = 0.00 (p < 0.05). CONCLUSION: C. fel-terrae leaves ethanol extract is effective to be used as an anti-inflammatory in patients after tooth extraction combined with amoxicillin 500 mg and mefenamic acid 500 mg.